Active release of pneumolysin prepores and pores by mammalian cells undergoing a Streptococcus pneumoniae attack - Wolfmeier, Heidi; Radecke, Julika; Schoenauer, Roman; Koeffel, René; Babiychuk, Viktoria S.; Drücker, Patrick; Hathaway, Lucy J.; Mitchell, Timothy J.; Zuber, Benoît; Draeger, Annette; Babiychuk, Eduard B. (Biochimica et biophysica acta, 2016)
Streptococcus pneumoniae is a potent human pathogen. Its pore-forming exotoxin pneumolysin is instrumental for breaching the host's epithelial barrier and for the incapacitation of the immune system. Using a combination of life imaging and cryo-electron microscopy we show that pneumolysin, released by cultured bacteria, is capable of permeabilizing the plasmalemma of host cells. However, such permeabilization does not lead to cell lysis since pneumolysin is actively removed by the host cells. The process of pore elimination starts with the formation of pore-bearing plasmalemmal nanotubes and proceeds by the shedding of pores that are embedded in the membrane of released microvesicles. Pneumolysin prepores are likewise removed. The protein composition of the toxin-induced microvesicles, assessed by mass spectrometry, is suggestive of a Ca2+-triggered mechanism encompassing the proteins of the annexin family and members of the endosomal sorting complex required for transport (ESCRT) complex. S. pneumoniae releases sufficient amounts of pneumolysin to perforate the plasmalemma of host cells, however, the immediate cell lysis, which is frequently reported as a result of treatment with purified and artificially concentrated toxin, appears to be an unlikely event in vivo since the toxin pores are efficiently eliminated by microvesicle shedding. Therefore the dysregulation of cellular homeostasis occurring as a result of transient pore formation/elimination should be held responsible for the damaging toxin action. We have achieved a comprehensive view of a general plasma membrane repair mechanism after injury by a major bacterial toxin. •S. pneumoniae releases sufficient PLY to perforate host cells.•PLY-induced plasmalemmal perforations are efficiently repaired.•Microvesicle shedding is the predominant mechanism of PLY-pore elimination.•PLY prepores are likewise removed.•Shed microvesicles are enriched in annexins and ESCRT proteins.